Effects of various carbohydrate sources on the utilization of low-quality tallgrass-prairie hay in continuous culture - J.S. Heldt; R.C. Cochran; C.P. Mathis; Evan C. Titgemeyer; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1998)
We evaluated the effects of supplemental carbohydrate sources on the utilization of low- quality forage in continuous "artificial rumen" culture. Providing readily digestible carbohydrates (starch, glucose, and fiber) did not improve total diet digestion. In fact, starch and glucose depressed fiber digestion. Response to other simple sugars was variable.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Digestion; Carbohydrate; Forage; Continuous culture